Chineseness as a competitive disadvantage: Singapore Chinese business strategies after failing in China - Heidi Dahles (Copenhagen Business School (CBS), Asia Research Centre (ARC), 2006)
The focus of this paper is on the strategies applied by Singapore-Chinese businesses upon failing in their China business ventures. It has been argued that both the increase of Singapore ventures into China and the failures are due to either cultural issues (misinterpretation of 'shared ethnicity') or economic factors (differences in economic practices). Singapore businessmen apply inclusive strategies combining Western management styles with Chinese ways of doing business in order to reduce the risk involved with investments across national borders into China. Though largely successful, this strategy entails its own risks. Based on 10 case studies, this paper discusses the ways in which Singapore Chinese entrepreneurs respond upon failing in China and the strategies they develop to re-find their comfort zone for transnational business ventures. Keywords: Chineseness, Ethinicity, Entrepreneurship, Singapore, China, Business Strategies.
hdl:10398/7401
Keywords: 330; entrepreneurship; kina; kulturelle forhold; international handel; forretningsmodeller; singapore